Hostage : a novel - Wiesel, Elie, 1928-2016 (Alfred A. Knopf, 2012)
It's 1975, and Shaltiel Feigenberg, a professional storyteller and writer, has been taken hostage. He has been abducted from his home in Brooklyn, New York, blindfolded and tied to a chair in a dark basement. His captors, an Arab and an Italian, don't explain why Shaltiel has been chosen, just that his life will be bartered for the freedom of three Palestinian prisoners. As his days of waiting commence, Shaltiel resorts to what he does best, telling stories to himself and to the men who hold his fate in their hands. A Communist brother and a childhood spent hiding from the Nazis in a cellar, the kindness of liberating Russian soldiers, the unrest of the 1960s are some of the memories that unfold during his captivity, as the outside world breathlessly follows his disappearance and the police move toward a final confrontation with his captors. The author builds the world of Shaltiel's memories, haunted by the Holocaust and a Europe in the midst of radical change. This story is both a thriller and a meditation on the power of memory to connect us to the past and our shared need for resolution.